Liquid–liquid interface induced PDMS‐PTFE composite membrane for ethanol perm‐selective pervaporation. Issue 8 (6th April 2022) - Li, Chong; Li, Jie; Cai, Peng; Cao, Tengxuan; Zhang, Nai; Wang, Naixin; An, Quan‐Fu
Abstract: Pervaporation has great potential in the separation of many significant mixtures. However, excessive penetration of separation layer into the substrate pores enhances the transport resistance of solvent molecules, which impedes the development of pervaporation membrane. In this study, a facile floating‐on‐water (FOW) method was used to prepare poly(dimethylsiloxane) (PDMS)/polytetrafluoroethylene (PTFE) composite membranes. The formation of separation layer and preparation of composite membrane were step‐by‐step completed through this liquid–liquid interface induced method. The PDMS layer thickness could be precisely regulated from 0.5 to 8 μm. Moreover, the pore penetration could be controlled by optimizing pre‐crosslinking density, crosslinking time on water and polymer solution volume. The obtained PDMS/PTFE composite membrane exhibited a high flux of 2016 g·m −2 ·h −1 with the separation factor of 12 when separating ethanol from a 5 wt% ethanol/water mixture. The performance of the membrane could be stable for over 200 h, exhibiting great potential in ethanol perm‐selective pervaporation.